2016 IEEE 55th Conference on Decision and Control (CDC) 2016
DOI: 10.1109/cdc.2016.7799445
|View full text |Cite
|
Sign up to set email alerts
|

Mixed monotonicity of partial first-in-first-out traffic flow models

Abstract: Abstract-In vehicle traffic networks, congestion on one outgoing link of a diverging junction often impedes flow to other outgoing links, a phenomenon known as the first-in-first-out (FIFO) property. Simplified traffic models that do not account for the FIFO property result in monotone dynamics for which powerful analysis techniques exist. FIFO models are in general not monotone, but have been shown to be mixed monotone-a generalization of monotonicity that enables similarly powerful analysis techniques. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 14 publications
0
30
0
Order By: Relevance
“…Secondly, we give two sufficient conditions that can be used to verify mixed monotonicity of a function defined on ndimensional Euclidean space. These sufficient conditions are more general than the ones given in [3], [5]. By our first sufficient condition, all continuously differentiable functions with bounded partial derivatives are mixed monotone.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Secondly, we give two sufficient conditions that can be used to verify mixed monotonicity of a function defined on ndimensional Euclidean space. These sufficient conditions are more general than the ones given in [3], [5]. By our first sufficient condition, all continuously differentiable functions with bounded partial derivatives are mixed monotone.…”
Section: Introductionmentioning
confidence: 93%
“…Moreover, it remains unclear how to verify the mixed monotonicity of a function or a system in general. Instead, there are only some sufficient conditions [3], [5] available for checking mixed monotonicity. Aimed at solving these challenges, we present two main contributions of this paper.…”
Section: Introductionmentioning
confidence: 99%
“…By assuming fully non-FIFO models, system becomes monotone in the whole state 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 space. For a more thorough discussion on physical aspects of monotonicity in traffic networks, see [15].…”
Section: B Monotonicitymentioning
confidence: 99%
“…Consequently, an increase in the occupancy of link 3 may actually decrease the occupancy of link 10. The authors in [17] studied this phenomenon and showed that traffic networks are mixed monotone, which is a weaker property than monotonicity. We desire that links do not impede the vehicular flow from their upstream links, i.e.…”
Section: Problem Statement and Approach A Motivating Applicatiomentioning
confidence: 99%